SPEAK Out! Day with Future Teachers Taking the Lead. Issue 4 (4th May 2018) - Watterson, Thomas; Wells, Gayle; Claxton, David; Grube, Dan
Abstract : Each year, health and physical education representatives converge at our nation's capital for the SHAPE America SPEAK Out! Day to advocate for health and physical education and its current initiatives. This endeavor has grown to include over 200 representatives from 46 different states. In recent years, this program has become very successful in recruiting teachers and administrators from all over the country to represent their states. What has been missing is the link for future teachers to be represented as well. This article discusses the importance of increasing the number of students and the direct connection that colleges and universities can make during this unique experience. Specifically, it describes how one university combined this powerful advocacy experience with its mission, which can serve as an example for other institutions to follow.